Staphylinidae Latreille 1802 ... - A. S., Sazhnev (Zenodo, 2018)
Список Staphylinidae КоманÁорских островов Omaliinae MacLeay, 1825 Arpedium brachypterum (Gravenhorst, 1802) Eucnecosum brunnescens (J. Sahlberg, 1871) [Ryabukhin, 1999; Αобкова, Семенов, 2017] Micralymma brevilingue Schiodte, 1845 [Ryabukhin, 1999] Olophrum boreale (Paykull, 1792) Olophrum consimile (Gyllenhal, 1810) [Ryabukhin, 1999; Αобкова, Семенов, 2017] Omalium strigicolle Wankowicz, 1869 ... : Published as part of A. S., Sazhnev, 2018, Materials to the rove beetles fauna (Coleoptera: Staphylinidae) of the Commander Islands (Kamchatka Region, Russia), pp. 19-23 in Caucasian Entomological Bulletin 14 (1) on page 22, DOI: 10.23885/1814-3326-2018-14-1-19-23, http://zenodo.org/record/13273991 ...